The Effectiveness of the Symbolic Modeling Method Helped by Profession Cartoon Puppet Media Against Language Skills and Storytelling Skills - Siti Elyasari; Achmad Buchori; Joko Sulianto (International Journal of Research in Education, 2023)
Teachers are required to be able to apply creative and innovative learning methods by utilizing media so that they can help develop students' language skills and storytelling skills. This study aims to determine the effect, learning completeness, and average difference of the symbolic modeling method assisted by professional cartoon puppet media on language skills and storytelling skills. Data collection methods used interviews, observation, and documentation. The data were processed the Manova test, learning completeness test, average difference test, and N-Gain Score test. The results showed the symbolic modeling method assisted by professional cartoon puppet media had an effect on language skills and storytelling skills, in terms of the multivariate test table and the table test of between subject effects on the manova test with each Sig. 0.000 < 0.05. The learning completeness test obtained a sig value. 0.002 on language skills and Sig. 0.032 on storytelling skills, because the value of Sig. < 0.05, it was concluded that the percentage of students who got posttest scores ≥ 75 was more than 75%. The average difference test obtained sig. 0.039 on language skills and sig. 0.001 on storytelling skills, because the value of Sig. <0.05 concluded that there is a difference in the mean of the two groups. The average N-Gain Score test is 0.71 for language skills, which is included in the high category, which means that interpretation is quite effective, and 0.67 for storytelling skills, which is included in the medium category, which means that interpretation is quite effective